KAEDAH KEDABITAN PERIWAYAT: KAEDAH AL-JARH WA TADHBIT - Muadilah Hs. Bunganegara; I Gusti Bagus Agung Perdana Rayyn (Qolamuna : Jurnal Studi Islam, 2023)
Abstract : Kedabitan is one of the requirements for categorizing a hadith, whether it is of valid, hasan or daif quality. The narrator's method of inheritance is a very important measurement tool in hadith research, especially in the aspect of the narrator's intellectual credibility. The existence of different views among hadith critic scholars in assessing the intellectual credibility of the narrator gave birth to the criteria for the narration of hadith narrators. This research focuses on redefining the understanding of "kedabitan" and the methods used in addressing differences in the intellectual credibility of narrators and differences of opinion among hadith critics in assessing the credibility of narrators. The purpose of this research is to provide an understanding related to the rules of obedience of hadith narrators, which will have implications for the quality of a hadith. This research is a literature research that is descriptive qualitative in nature, by collecting relevant literature and information in order to prove the accuracy of a study, and not cause any confusion in the hadith narration process. So that the results of this study, namely the hadith critic scholars have some fundamental differences in addressing the credibility of hadith narrators, namely in terms of the method used as a measuring tool, the pronunciations of the narrator's assessment of the authenticity of the narrator as an analytical knife and the method of analyzing the authenticity of the narrators of hadith as a form of effort to find out and ensure that the hadiths are truly sourced from the Prophet. Keywords : Dabit, Narrator, Al-Jarh, Tadhbit